AFASTAMENTO E RETORNO ÀS ATIVIDADES DE PROFISSIONAIS DE SAÚDE NO CONTEXTO DA COVID-19 - Oliveira, Emerson Roberto de; Nasser, Matheus Arouca; Guimarães, Rafael Luis Mol; Maia, Raphael Lázaro; Patrick, Thaylan; Pimenta, Hugo (Sinapse Múltipla, 2020)